2014
DOI: 10.1002/2013wr014830
|View full text |Cite
|
Sign up to set email alerts
|

Constraining a compositional flow model with flow‐chemical data using an ensemble‐based Kalman filter

Abstract: Isothermal compositional flow models require coupling transient compressible flows and advective transport systems of various chemical species in subsurface porous media. Building such numerical models is quite challenging and may be subject to many sources of uncertainties because of possible incomplete representation of some geological parameters that characterize the system's processes. Advanced data assimilation methods, such as the ensemble Kalman filter (EnKF), can be used to calibrate these models by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 54 publications
(68 reference statements)
2
34
0
Order By: Relevance
“…Such a separation of the update steps is expected to provide more consistent estimates of the parameters. The dual update framework was indeed shown to provide better performances than the joint EnKF, at the cost of increased computational burden (see for instance, Moradkhani et al, 2005b;Samuel et al, 2014;Gharamti et al, 2014a).…”
Section: The Dual Enkfmentioning
confidence: 99%
See 2 more Smart Citations
“…Such a separation of the update steps is expected to provide more consistent estimates of the parameters. The dual update framework was indeed shown to provide better performances than the joint EnKF, at the cost of increased computational burden (see for instance, Moradkhani et al, 2005b;Samuel et al, 2014;Gharamti et al, 2014a).…”
Section: The Dual Enkfmentioning
confidence: 99%
“…One classical approach that has been proposed to tackle this issue is the so-called dual filter, which separately updates the state and parameters using two interactive EnKFs, one acting on the state and the other on the parameters (Moradkhani et al, 2005b). The dual EnKF has been applied to streamflow forecasting problems using rainfall-runoff models (e.g., Lü et al, 2013;Samuel et al, 2014), subsurface contaminant (e.g., Tian et al, 2008;Lü et al, 2011;Gharamti et al, 2014b), and compositional flow models (e.g., Phale and Oliver, 2011;Gharamti et al, 2014a), to cite but a few. Gharamti et al (2014a) concluded that the dual scheme provides more accurate state and parameter estimations than the joint scheme when implemented with large enough ensembles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data assimilation (DA) methods follow a Bayesian formulation by combining prior information of a dynamical system with available measurements to obtain an analysis of the system state and parameters (Hoteit et al, 2012;Gharamti et al, 2014a). Sequential DA techniques, such as the ensemble Kalman filter (EnKF), assimilate the data as they become available.…”
Section: E Gharamti Et Al: Hybrid and Esos-based Enkf Formulationsmentioning
confidence: 99%
“…The complexity of the forecast step grows with the ensemble size. If one supposes that C M is the cost for integrating the model to the next observation time, the computational requirement of the forecast step is NN e C M , where N is the final simulation time (Gharamti et al, 2014a). The superscripts a, f and i denote the analysis, forecast and ensemble number, respectively.…”
Section: The Ensemble Kalman Filter For State-parameter Estimationmentioning
confidence: 99%